Memorial de formação: da entrada na escola ao ingressar no magistério em ambiente amazônico - Pinheiro, Jorge Pinto (Brasil, 2024)
The present final work of conclusion was built in the form of a Memories has as a partial requirement to obtain the title of degree in Pedagogy, this work aims to rescue memories that are part of the personal and academic trajectory and at the same time elucidate a subject pertinent to the exercise of teaching, valuing the use of autobiographical writing as a contribution to research in teacher training. This study Will address topics such as the interrelationship between learning and reflections on teaching practice and teaching challenges. The work is structured in an introduction that describes the Academic Memory, in which the author makes a brief reflection of his school trajectory, in chapter 1 – from entry into school to entry into teaching in the Amazon Environment, in chapter 2 – academic training at a higher level, in chapter 3 – reflections on teaching practice and school management and in chapter 4 – final considerations.